Response Surface Optimization of a Plastic Powder Processing Machine using Desirability Function Approach - Nwogu, C. N.; Remy, U.; Igbokwe, J. O.; Okoronkwo, A. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Optimal performance and operational parameters of a plastic powder processing machine used for converting used PET bottles into powdered form was assessed in this study. The geometrical (operational) parameters investigated include: speed of hammermill shaft, number of blades on the hammermill, length of hammermill blade and intrinsic viscosity of the PET processed while grain size produced, throughput and conversion efficiency constitute the machine’s (performance) parameters. The interactions of these factors (operational parameters) and responses (performance parameters) were evaluated and estimated using a completely randomized Box-Behnken blocked design layout which comprises twenty seven (27) experimental runs. Desirability function approach was the optimization technique applied. Results revealed the optimal values of hammermill speed, number of blades, blade length and intrinsic viscosity as 1400 rpm, 4, 109.6 mm and 0.82798 respectively with responses of 89.71%, 1.9953 kg/min and 139.9998 for conversion efficiency, throughput and grain size respectively. These optimal operational parameters will make the machine economical to operate in terms of labour, time and energy requirement.